2021
DOI: 10.3389/fmars.2021.671390
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Study of Trace Element Concentrations in Sediments of the Intertidal Zone of Amazonian Oceanic Beaches

Abstract: Analyzing the presence and quantifying trace elements is of paramount importance to understand natural environmental processes and monitor the degree of anthropogenic disturbance to mitigate impacts already caused. Here, we aimed to establish a baseline of the trace elements profile and concentrations in sandy sediments of intertidal areas of three Amazonian beaches (Brazil). For each beach, sediments were collected from three different sectors (south, center, and north) and five shoreline distance levels (fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Similarly, Santos et al [19] recorded a total of 46 species in the intertidal area of Atalaia, Farol-Velho, and Corvina Beaches, all sites also located on the Pará coast. Given that (i) macrotidal dissipative beaches are expected to host a larger number of species and individuals among beach types [46,47] and (ii) that the study area is not subject to a high degree of anthropic influence, such as urbanization, tourism, or trace element contamination [7,28], factors often associated with decreased macrobenthic diversity [48][49][50][51], our results are unexpected and suggest this overall low diversity is not a regional but rather an intrinsic feature of local beaches. Similarly, Jourde et al [52] found low macrobenthic diversity (H' means ranging from 0.17 to 1.74) on mudflats of Guiana.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similarly, Santos et al [19] recorded a total of 46 species in the intertidal area of Atalaia, Farol-Velho, and Corvina Beaches, all sites also located on the Pará coast. Given that (i) macrotidal dissipative beaches are expected to host a larger number of species and individuals among beach types [46,47] and (ii) that the study area is not subject to a high degree of anthropic influence, such as urbanization, tourism, or trace element contamination [7,28], factors often associated with decreased macrobenthic diversity [48][49][50][51], our results are unexpected and suggest this overall low diversity is not a regional but rather an intrinsic feature of local beaches. Similarly, Jourde et al [52] found low macrobenthic diversity (H' means ranging from 0.17 to 1.74) on mudflats of Guiana.…”
Section: Discussionmentioning
confidence: 68%
“…Sampling was performed during spring tides at the eastern section of Goiabal Beach (2°31′02.2 N; 50°49′33.8 W), and the western section of Nazaré (2°29′32.3 N; 50°47′23.2 W) and Samaúma Beaches (2°48′23.0 N; 50°55′40.9 W) (Figure 1). The three sites are tidedominated flats with a predominance of very fine sands [28]. The width of the sandy intertidal zone changes across the arc, shorter eastwards, where the stream sediment is responsible for muddy lower levels.…”
Section: Study Area and Sampling Proceduresmentioning
confidence: 99%
“…Accumulation of TEs in marine sediments depends on various factors, e.g., water depth, water physicochemical properties (pH, salinity, temperature, dissolved oxygen and organic matter content), sediment composition and texture, intensity/direction of winds, waves, and currents, fluvial, atmospheric, and other natural or anthropogenic inputs (Oros, 2019;Constantinescu et al, 2023). Multivariate analysis, especially PCA, is widely used to identify the main factors affecting the concentration of TEs in sediments and possible pollution sources/transport pathways (Martins et al, 2012;Kahal et al, 2018;Remeikaite-Nikienėet al, 2018;El-Sorogy et al, 2020;Perumal et al, 2021;Vilhena et al, 2021;Wang et al, 2021;Kubra et al, 2022;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this reduction in the anthropogenic input of classic contaminants, these are still frequently persistent in the environment, with the added threat of newly emerging contaminants such as microplastics, pharmaceuticals and personal care products [ 3 ]. The prevalence and consequent significant mobility of these contaminants in the ecosystems [ 4 ] can even be detected in remote uninhabited locations, with an unexpected presence in key trophic compartments such as the planktonic microbial community [ 5 , 6 ]. Beyond the necessary environmental risk assessment (ERA) approaches, to evaluate the possible impacts of these contaminants in the different biotic compartments [ 7 ], it is also essential to understand how these xenobiotics interact with the organisms and what are the molecular implications of these interactions.…”
Section: Introductionmentioning
confidence: 99%